2020
DOI: 10.1158/1940-6207.capr-20-0109
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Provider Beliefs and Recommendations About Colorectal Cancer Screening in Four Healthcare Systems

Abstract: ◥Primary care provider's (PCP) perceptions of colorectal cancer screening test effectiveness and their recommendations for testing intervals influence patient screening uptake. Few large studies have examined providers' perceptions and recommendations, including their alignment with evidence suggesting comparable test effectiveness and guideline recommendations for screening frequency. Providers (n ¼ 1,281) within four healthcare systems completed a survey in 2017-2018 regarding their perceptions of test effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…This study provides important information about beliefs among American family medicine and internal medicine physicians regarding effectiveness of various types of cancer screening. Overall, the rates of perceived effectiveness were lower than other reports in the last decade ( Ghai et al, 2020 , Khairy et al, 2018 , Lewis et al, 2015 , Raz et al, 2018 ), perhaps related in part to the fact that the current data are more recent and from a national sample. Results suggest that a majority of physicians support colonoscopy for colorectal cancer screening, which is consistent with previous studies and recommendations ( Brown et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…This study provides important information about beliefs among American family medicine and internal medicine physicians regarding effectiveness of various types of cancer screening. Overall, the rates of perceived effectiveness were lower than other reports in the last decade ( Ghai et al, 2020 , Khairy et al, 2018 , Lewis et al, 2015 , Raz et al, 2018 ), perhaps related in part to the fact that the current data are more recent and from a national sample. Results suggest that a majority of physicians support colonoscopy for colorectal cancer screening, which is consistent with previous studies and recommendations ( Brown et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 67%
“…It is likely that perceived effectiveness is associated with, but not identical to, screening referral rates. For example, one study found that 82.9% of primary care providers rated colonoscopy as very effective ( Ghai et al, 2020 ), and 77.9% recommended colonoscopy to patients. Additionally, it is well-known that screening recommendations or referrals do not necessarily translate into actual screening completion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this was a cross-sectional study, this difference is important and suggests that public health interventions should focus efforts to increase colorectal cancer screening in rural areas. It is important to note that while colonoscopy is reported as favored and the most recommended modality by primary care practitioners, 26 , 27 it may not be the best solution in rural communities, where travel and access barriers are pronounced for colorectal cancer screening. 28 , 29 Newer stool-based tests, like fecal immunohistochemical tests, might be more acceptable to rural residents and can address issues with respect to access barriers in rural communities.…”
Section: Discussionmentioning
confidence: 99%
“…CRC screening preferences appear to be misaligned between clinicians and patients: whereas clinicians tend to prefer screening colonoscopy over stool-based tests (13)(14)(15)(16), when given options, patients tend to prefer stoolbased tests over screening colonoscopy (17,18). Although research is extensive on patient, clinician, and health care system factors associated with CRC screening completion, data on clinician recommendation of guideline-endorsed CRC screening methods and factors associated with guideline-consistent screening recommendations are sparse (19,20). A 2007 survey of a nationally representative sample of primary care clinicians (PCCs) showed that less than 20% made guideline-consistent recommendations across all CRC screening methods (19).…”
Section: Introductionmentioning
confidence: 99%